Web services for e-Procurement system in the context of supply chain management / Yap Khay Seng - Yap, Khay Seng (2007)
The current Information Technologies (IT) such as Electronic Data Interchange (EDI) and Enterprise Application Integration (EAI) have been used by major organizations to integrate the business processes in the supply chain. However, these technologies are expensive, inflexible and not dynamic. Web Services seem to be a way to solve these problems. By using the standard internet protocol, Web Services can easily provide interoperable software service functions that can be accessible by various hardware and platform, even passing through the firewalls. The purpose of this project is to develop a system using Web Services to implement real time information sharing and dynamic procurement operations in the context of Supply Chain Management. Web Services for E-Procurement (WSEP) System is a web-based procurement system that provide real time knowledge sharing and procurement operations. The system is deployed using Web Services which is not only easier to implement but also integrated well with legacy system. The system is running under the Microsoft .NET 1.1 Framework and Microsoft SQL Server 2000 as the backend database.